Antibacterial Potential of Symmetrical Twin-Drug 3,6-Diaminoxanthones - Diana I. S. P. Resende; Fernando Durães; Sidika Zubarioglu; Joana Freitas-Silva; Nikoletta Szemerédi; Madalena Pinto; Eugénia Pinto; Paulo Martins da Costa; Gabriella Spengler; Emília Sousa (MDPI AG, 2024)
Global health faces a significant issue with the rise of infectious diseases caused by bacteria, fungi, viruses, and parasites. The increasing number of multi-drug resistant microbial pathogens severely threatens public health worldwide. Antibiotic-resistant pathogenic bacteria, in particular, present a significant challenge. Therefore, there is an urgent need to identify new potential antimicrobial targets and discover new chemical entities that can potentially reverse bacterial resistance. The main goal of this research work was to create and develop a library of 3,6-disubstituted xanthones based on twin drugs and molecular extension approaches to inhibit the activity of efflux pumps. The process involved synthesizing 3,6-diaminoxanthones through the reaction of 9-oxo-9H-xanthene-3,6-diyl bis(trifluoromethanesulfonate) with various primary and secondary amines. The resulting 3,6-disubstituted xanthone derivatives were then tested for their in vitro antimicrobial properties against a range of pathogenic strains and their efficacy in inhibiting the activity of efflux pumps, biofilm formation, and quorum-sensing. Several compounds have exhibited effective antibacterial properties against the Gram-positive bacterial species tested. Xanthone 16, in particular, has demonstrated exceptional efficacy with a remarkable MIC of 11 µM (4 µg/mL) against reference strains Staphylococcus aureus ATCC 25923 and Enterococcus faecalis ATCC 29212, and 25 µM (9 µg/mL) against methicillin-resistant S. aureus 272123. Furthermore, some derivatives have shown potential as antibiofilm agents in a crystal violet assay. The ethidium bromide accumulation assay pinpointed certain compounds inhibiting bacterial efflux pumps. The cytotoxic effect of the most promising compounds was examined in mouse fibroblast cell line NIH/3T3, and two monoamine substituted xanthone derivatives with a hydroxyl substituent did not exhibit any cytotoxicity. Overall, the nature of the substituent was critical in determining the antimicrobial spectra of aminated xanthones.